KEBERAGAMAN SIFAT FISIK, KANDUNGAN GIZI DAN KADAR ASAM SIANIDA BEBERAPA KACANG ARBILA (Phaseolus lunatus L) TIMOR - Ratna Wati Marina Theon; Herianus J. D. Lalel; Yuliana Tandi Rubak (Politeknik Pertanian Negeri Kupang, 2022)
Arbila beans (Phaseolus lunatus L.) are one of the wild beans found on Timor Island. Local people utilize the beans even though they contain cyanide acid toxic. To underpin the nutritive as well as the toxic content of the bean, a study has been conducted using four types of the bean found in Timor i.e. red bean, black bean, white bean, and brown bean. The red bean has a middle size and looks a bit swollen; the black bean is a lengthy middle size; the white bean is also lengthy but looks flat; while the brown bean is a bit broad and enlarged. All bean types contain protein of about 17%, calcium 39-42.5 mg per 100 g; while the highest lipid content (10.86%) was found in the brown beans. Cyanide acid content was found very high in the black bean (244.71 ppm), on the contrary, its lowest content was found in the white bean (34.30 ppm). Keywords: Arbila bean (Phaseolus lunatus L.), nutritive value, cyanide acid.